Jihad: Meaning, Essence, and Contextualization of Revolutionary Experience Hadratussyaikh K.H. Hasyim Ash'ari - Taufiqurrohman, Muhammad; Islami, Aprilia Nur; Muhaemin, Muhaemin; Hasanah, Sri Nur (STAI AL-FALAH CICALENGKA, 2022)
The term jihad has various meanings, not only connoting the meaning of